Application of overnight places near UiTM / Muhamad Nurman Aqif Muhamad Mazli ... [et al.] - Muhamad Mazli, Muhamad Nurman Aqif; Azman, Nur Alissa Natasya; Abdul Razak, Nurul Afiesya; Zulkifli, Nur Laila Khadijah; Mohammad Jaafar, Muhammad Haiqal (2024)
The "UiTM 360" app is specifically designed to assist UiTM tourists and families seeking accommodation near UiTM campuses. With a focus on convenience and accessibility, the app categorizes hotels based on their proximity to UiTM, ranging from 10 km to 50 km in distances. Targeting UiTM visitors and families, the app aims to provide a seamless experience by not only recommending nearby hotels but also highlighting essential facilities such as mosques, restaurants, laundromats, and convenience stores in the vicinity. By offering insights into the surrounding area, the app provides users with well-informed details about their hotel's location and nearby amenities, enhancing their overall stay and experience. The objective of this project is to ensure that users visiting from other places have an idea of where they would like to stay overnight. By achieving the full potential use of this application, it is stipulated to help other users as well.